2005
DOI: 10.1016/j.vacuum.2005.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation in SiSb system

Abstract: Thermal annealing of Si/Si 1-x Sb x /Si amorphous thin film tri-layer samples (x=18 and 24 at%Sb) under 100 bar Ar pressure results in an interesting pattern formation. In pictures, taken by means of cross-sectional transmission electron microscopy (TEM), stripe-shaped contrast, with three maxima, parallel with the interfaces can be seen. Secondary neutral mass spectrometer (SNMS) measurements revealed that the regions with different contrasts correspond to Sb-rich and Sb-depleted regions. Furthermore, the Sb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It was showed that sample with 5% Sb concentration annealed lower then 823 K remains 6 in amorphous state. From the time evaluation of SNMS concentration profile D Sb ≈1•10 -21 m 2 /s diffusion coefficient was calculated for Sb diffusion in amorphous Si at 823 K. As it was described in our present and previous works [5,6] in annealed samples the diffusion and decomposition processes significantly enhanced by the applying small (100 bar) hydrostatic pressure. The effect of hydrostatic pressure is not clear and need further investigation.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It was showed that sample with 5% Sb concentration annealed lower then 823 K remains 6 in amorphous state. From the time evaluation of SNMS concentration profile D Sb ≈1•10 -21 m 2 /s diffusion coefficient was calculated for Sb diffusion in amorphous Si at 823 K. As it was described in our present and previous works [5,6] in annealed samples the diffusion and decomposition processes significantly enhanced by the applying small (100 bar) hydrostatic pressure. The effect of hydrostatic pressure is not clear and need further investigation.…”
Section: Discussionmentioning
confidence: 54%
“…), which means that Sb diffused out from SiSb layer into amorphous Si. However, in contrast to heated samples in 100 bar Ar with higher Sb concentration (13-26 at%) [6], where the SiSb layer underwent a spinodal-like decomposition resulting three Sb-rich stripes parallel to the original interfaces, morphological changes were not detected. Electron diffraction measurements also showed that the samples heat treated at 823 K remained in amorphous state.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…%, where insulators are defined as having zero conductivity with an activated temperature dependence in the limit as T goes to zero and metals have finite, nonzero conductivity, and power law dependence in the same limit. [7][8][9][10] In a recent paper, 11 we showed that annealed a-Nb-Si develops Nb-rich clusters within a Nb-depleted amorphous matrix, causing the resistivity to increase dramatically and leading to improvements in the technological use of a-Nb-Si resistance thermometers. % Gd; 2-6 this alloy also shows dramatic magnetic and magnetotransport effects, including enormous ͑many orders of magnitude͒ negative magnetoresistance 3,4 ͑MR͒ below a characteristic temperature T * .…”
Section: Introductionmentioning
confidence: 99%